Damping of low-frequency oscillation using renewable generation units; Energy Reports; Vol. 9, supp. 8 : The 3rd International Conference on Power Engineering (ICPE 2022) - Ufa R. A. Ruslan Alexandrovich (2023, 2023)
Nowadays there is a significant increase the number of generation units based on renewable energy sources in electric power systems, the main goal of which is to ensure global access to affordable, reliable, sustainable and modern sources of energy. However, as the penetration level of renewable generation units increases, there are power oscillations easily occur, which create biggest challenges for the power system stability. In particular, the dominant modes of modern generation units, connected to the main grid via a voltage source converter, are in the range of higher frequencies than electromechanical oscillations. Consequently, the chance of occurrence of low-frequency oscillations increases, the parameters and the trajectory of which will differ from power oscillations in power system without renewables. The results of the analysis of low-frequency oscillation parameters in part of Eastern Siberia power system and evaluation of impact of renewable generation unit on power oscillations are presented in this article. The results were obtained by the Hybrid real time simulator based on the combination of analog, physical and digital modeling levels. The developed scheme of part of Eastern Siberia power system and simulation results were verified by SCADA system. The difference between the results of simulation and SCADA system did not exceed 1%. It indicates the adequacy of the Hybrid real time simulator and the developed scheme of power system. Based on the evaluation of the parameters of power oscillations and the calculation of the degree of damping of the transient process, it can be noted that the oscillatory stability of the power system is improved: damping time decreases, the damping ratio increases with increasing of renewables penetration level.